Fremde Vergangenheit: Zur Orientalistik des Göttinger Gelehrten Johann David Michaelis (1717-1791) - Rauchstein, Maike (transcript, 2017)
On the cultural contact between Germany and the Orient in the 18th century, and one of the most significant - if also controversial - founders of Oriental Studies.